2019
DOI: 10.1186/s13104-019-4434-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on skill and health related physical fitness characteristics between national basketball and football players in Sri Lanka

Abstract: Objective To compare health and skill related physical fitness profiles between healthy, male, basketball and football players of Sri Lankan national teams. Results Thirty basketball players (mean age 24 ± 4.5 years) and 30 football players (mean age 23 ± 4.3 years) were evaluated for health related fitness characteristics (body fat percentage, cardio-respiratory fitness, isometric hand grip strength, lower body and upper body muscular strength, abdominal and upper body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…4 (centres), and mean team measurements are provided in Table 2 of the ESM. The most frequently implemented test and outcome variable used across studies were the sum of skinfolds at three sites (chest, abdomen, and thigh [16,[53][54][55][56][57][58], triceps, pectoral, and subscapular [59], and triceps, abdomen, and thigh [4,21,60]) and body fat percentage, respectively (Table 3…”
Section: Anthropometric Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 (centres), and mean team measurements are provided in Table 2 of the ESM. The most frequently implemented test and outcome variable used across studies were the sum of skinfolds at three sites (chest, abdomen, and thigh [16,[53][54][55][56][57][58], triceps, pectoral, and subscapular [59], and triceps, abdomen, and thigh [4,21,60]) and body fat percentage, respectively (Table 3…”
Section: Anthropometric Characteristicsmentioning
confidence: 99%
“…Muscular power was assessed predominantly using jump tests, with 80 (58%) of the 137 studies in this review employing 18 different jump tests ( Two throwing tests were also used in studies to assess muscular power including a seated basketball throw [68] with speed (km/hour) of the throw taken as the outcome variable, and a seated medicine ball throw (1 kg [87,89] and unknown mass [56]) with horizontal displacement (m) of the ball used as the outcome variable. Additionally, muscular power variables were also recorded during tests predominantly implemented to assess strength.…”
Section: Muscular Powermentioning
confidence: 99%
“…Our study found that agility assessed by the burpee squat test score(nos) of BBP was 19. 15 to compare skill and health related fitness parameters in Srilankan Basketball players and football players. But studies on flexibility and agility of Indian players between these three groups are not found in literature standards.…”
Section: Discussionmentioning
confidence: 99%
“…Football is a popular sport and is played by more than 265 million people around the world 1 . This sport requires almost all aspects of physical fitness, both health-related and skills related fitness in the game 2 .Physical fitness is an important foundation so that football players can apply the skills and tactics that they have trained efficiently in a match. Studies show that low physical fitness will reduce performance and increase the risk ofinjury [3][4].…”
Section: Introductionmentioning
confidence: 99%